The physical and electrochromic properties of Prussian Blue thin films electrodeposited on ITO electrodes - Isfahani, V. Bayzi (2019)
In this article, a set of Prussian Blue (PB) thin films with different electrodeposition times (25 s, 50 s, 75 s, 100 s and 150 s) in air at ambient temperature was prepared. The layers were characterized by a variety of techniques which include, field effect scanning electron microscopy, energy-dispersive X-ray spectrometer, X-ray diffraction, Fourier transform infared spectroscopy, UV-Vis spectrophotometry, and electrochemical analysis. A simple and exact electrochemical method was used to estimate the optimal voltages for coloring and bleaching of different PB layers. Controlling electrodeposition time along with applying suitable voltage enabled us to investigate and improve electrochromic properties of PB layer. The sample prepared under 75 s deposition time showed probably a composition intermediate between the insoluble and soluble form. Furthermore, this sample (S75) shows a better electrochromic properties. High value of electrochromic contrast 55.36% at 555 nm and well stability of ion exchange by cycling are the characteristics of this layer. The control of the deposition time resulted in an increase of 9.38 times of the contrast ratio and corresponding values for optical density (Delta OD) of the PB layers.